DAMPAK LAYANAN SYARIAH (OFFICE CHANNELING) TERHADAP PERTUMBUHAN ASET, KENAIKAN DANA PIHAK KETIGA (DPK), DAN KINERJA KEUANGAN PADA UNIT USAHA SYARIAH (UUS) TAHUN 2012-2016 - PUTRI ALIZA, YASHINTA; WURYANI, ENI (Jurnal Akuntansi AKUNESA, 2018)
Sharia Services (Office Channeling) as an alternative policy to expand market share of Islamic banking in Indonesia. This study aims to determine the impact of office channeling on asset growth, Third Party Funds (TPF), and financial performance. The data analysis technique used in this study is simple linear regression analysis. The results of the study show that office channeling has no effect on asset growth. This is because office channeling only carries out fundraising activities, while funding is carried out at Sharia Branch Offices (KCS). The results of the second study showed that office channeling had a positive effect on Third Party Funds (TPF) and the results of the third study showed that office channeling had a negative effect on financial performance.Keywords: Sharia Services (Office Channeling), Asset Growth, Third Party Funds, Financial Performance